Development of a prognostic model based on ferroptosis-related genes for colorectal cancer patients and exploration of the biological functions of NOS2 in vivo and in vitro - Li, Hongming; Feng, Xiaochuang; Hu, Yong; Wang, Junjiang; Huang, Chengzhi; Yao, Xueqing (Frontiers in Oncology, 2023)
Background Ferroptosis is involved in many malignant tumors and has been implicated in important mechanisms of colorectal cancer (CRC) suppression. However, the prognostic and predictive values of the ferroptosis activation pattern in CRC patients have not been noted. Here, we aimed to construct and validate a prediction model based on ferroptosis-related genes (FRGs) for CRC patients and investigated the expression pattern and biological function of the most significantly altered gene. Methods A total of 112 FRGs were obtained from the FerrDb website, and the clinical characteristics of 545 CRC patients and their global gene expression profiles were downloaded from The Cancer Genome Atlas (TCGA) database. Survival-related FRGs were identified by Cox proportional hazards regression analysis. Finally, the expression pattern and biological function of NOS2, the most implicated gene was explored in vitro and in vivo. Results The prediction model was established based on 8 FRGs. Patients in the high- or low-risk group were stratified based on the median risk value calculated by our model, and patients in the high-risk group experienced poor overall survival (p<0.01). Further validation demonstrated that the FRG model acted as an independent prognostic indicator for CRC patients (HR=1.428, 95% CI, 1.341-1.627; p<0.001). The area under the receiver operating characteristic (ROC) curve (AUC) for 5-year survival was 0.741. NOS2 was one of the most significantly affected FRGs and was highly expressed in malignant tissue, but it inhibited tumor growth and induced tumor cell death in vitro and in vivo, possibly by repressing the NF-κB pathway. Conclusion Our study revealed that FRGs have potential prognostic value in CRC patients and that NOS2 suppresses tumor progression, providing a novel therapeutic target for CRC treatment based on ferroptosis.